PENGARUH JEJARING SOSIAL DAN LINGKUNGAN SEKOLAH MELALUI MOTIVASI TERHADAP PRESTASI BELAJAR KETERAMPILAN KOMPUTER DAN PEGELOLAAN INFORMASI (KKPI) SISWA SMK NEGERI SAMARINDA UTARA. - Ratna Khairunisa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
This research was to find (1) influence of social network by a motivation on student’s achievement in computer and management information subject (2) the influence of school environment by a motivation on student’s achievement in computer and management information subject (3) the influence of motivation on student’s achievement in computer and management information subject (4) the influence of social network and school environment by a motivation which was involved with student’s achievement on Computer and Management Information subject. The research was held on vocational high school in North Samarinda. The respondents research were from the sample of students is 100 students. Data collecting technique used assessment scale and student’s achievement on computer and management information subject. Data analysis technique were used path analysis. Data were analyzed by using SPSS. The researcher found that (1) there was influence between social network (X1) by a motivation (X3) on student achievement (Y) the presentage is 34,9% ρx3x1 value it had significant relationship. (2) there was influence between school environment (X2) by a motivation (X3) on student achievement (Y) the presentage is 35,4% ρx3x2 value it had significant relationship. (3) there was influence between a motivation (X3) on student achievement (Y) the presentage is 22,5% ρx3 value it had significant relationship. (4) there was influence between of social network and school environment by a motivation with student’s achievement on Computer and Management Information subject the presentage is 85% R-square value and it had significant relationship. Based on the calculation and analysis can be made the conclusion, there is influence between of social network and school environment by a motivation had strong effect on the student’ achievement on Computer and Management Information subject on vocational high school in North Samarinda. Keywords: Social Network, School Environment, Motivation, Student Achievement.